Produksi Isolat Cendawan Mikoriza Arbuscular (CMA) dari Lahan Sayuran dan Lahan Semak di Sumberjaya Lampung Barat - Muhamad Gary Ranchiano; Maria Viva Rini (Jurnal WACANA PERTANIAN, 2018)
Mycorrhizal isolates production is strongly influence by the content of P, the type of host plant are used as well as the planting medium used. The use of diffrent types of host plant in this study include: Corn, Sorghum, Calopogonium  mucunoide CM, Centrocema pubescent CP, and than Pureraria javanica PJ was planted with method trapping culture is expected to have some kind of best host plant for propogation mycorrhizal spores.Used some of the planting medium include: zeolite,peat,and sand is expected to obtain a planting medium suitable for propogation of spores of mycorrhizal especially with single spore method. This research  intend to: 1) Calculated the popolation of mycorrhiza in several diffrent types of land use the vegetables patch and bush land before and after trapping. 2) Determine the difersity of AMF in the soil in vegetables farm and bush land.This Research ,soil samples for both studies were drawn from the second village Bodong Jaya districts Sumber jaya, West Lampung. Soil samples are taken to the Laboratory Production of Plantation Agriculture Faculty, Lampung University for sequel processing. This Reseach began in May until September 20016. . For the Reseach , the design of the treatment used was Factorial Design 5x 12. The First factor is the host plant (5 type). The Second factor is the land of origin  of the two types of land use (12 type). Treatment was repeated 4 times and applied to the experimental unit using Complete Randomized Group Design (RKTS),The Research  shows that the popolation of mycorrhiza on vegetables farms is higher than on the bush land before and after trapping is done. Type and spore types that are found on land planted with vegetables that host more corn and diverse than on land planted with vegetables that other host plant. Bush land has a diversity of types of spore and spore popolation fewer.  Finally Results  showed that the use of host plant maize and sorghum a like give the best results is developing CMA . Growing media use zeolite provide the best results for the parameter root infections and spore CMA compared with peat and sand media. Zeolite media best in symbiosis with the host plant sorghum, while the zeolite and  peat media by using a suitable host plant corn for the production of  CMA.